(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
It seems to us that it is most logical to consider the vocabulary from the point of view of the transformations used to create an equivalent translation. It is especially important, in our opinion, that unusual, not the most obvious transformations are not left without attention